Drug-induced pulmonary artery hypertension - O. D. Ostroumova; A. I. Listratov; A. I. Kochetkov; S. A. Bliznyuk; A. G. Komarova; D. A. Sychev (Izdatelstvo OKI, 2022)
Pulmonary arterial hypertension is a condition characterized by an increase in mean pressure in the pulmonary artery. This pathology is associated with high mortality, and specific therapy for pulmonary arterial hypertension does not affect the cause of the disease and is extremely expensive. In this regard, it is especially important to study the modifiable etiological factors of pulmonary arterial hypertension. One such factor is drugs. One of the leading groups of drugs-inductors is anorexigenic drugs. It was the representatives of this group, such as aminorex, who were the first inducers of pulmonary hypertension. Moreover, this adverse reaction was so significant that it led to the withdrawal of these drugs. Currently, the leading role in the context of drug-induced pulmonary hypertension is played by such drugs as anticancer, antiviral drugs, and interferons. These drugs lead to pulmonary hypertension through various pathophysiological mechanisms. The leading measures to prevent this pathology are to limit the use of culprit medications, reduce the spread of HIV infection, since several groups of drugs can be used to treat HIV-infected patients, leading to the development of pulmonary hypertension.